2007
DOI: 10.1016/j.juro.2007.03.178
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Magnetic Resonance Imaging Demonstrates Linear Growth of the Human Fetal Kidneys During Gestation

Abstract: This prenatal magnetic resonance imaging study demonstrates linear growth of the bipolar and anteroposterior diameters of human fetal kidneys in relation to gestational age. In addition, it is clear that bipolar diameter grows twice as rapidly as anteroposterior diameter and there is less variability for bipolar diameter. These normative curves may allow us to detect abnormal fetal evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Our study showed no significant gender effect on renal volumes, a finding also reported by Vlajković et al (2006). In several reports, no significant differences could be identified between the left and right fetal kidney size (Cohen et al , 1991; Hsieh et al , 2000; Yu et al , 2000; Witzani et al , 2006; Cannie et al , 2007; Shin et al , 2007; Tedesco et al , 2009). In our study, only for fetuses of GA ≥ 30 weeks, the right kidneys were slightly larger in volume compared to the left side.…”
Section: Discussionmentioning
confidence: 97%
“…Our study showed no significant gender effect on renal volumes, a finding also reported by Vlajković et al (2006). In several reports, no significant differences could be identified between the left and right fetal kidney size (Cohen et al , 1991; Hsieh et al , 2000; Yu et al , 2000; Witzani et al , 2006; Cannie et al , 2007; Shin et al , 2007; Tedesco et al , 2009). In our study, only for fetuses of GA ≥ 30 weeks, the right kidneys were slightly larger in volume compared to the left side.…”
Section: Discussionmentioning
confidence: 97%
“…Most of our knowledge about the value of MRI in assessing renal abnormalities comes from single case reports or small case series. 38-42 MRI is considered safe during pregnancy, and there are no reports of adverse fetal effects from short-term exposure to electromagnetic fields. Most safety studies have been done at 1.5 Tesla (T), and although approved by the U.S. Food and Drug Administration, the potential increase in the temperature of the amniotic fluid with 3T imaging should be considered.…”
Section: Diagnostic and Prognostic Aspectsmentioning
confidence: 99%
“…Most safety studies have been done at 1.5 Tesla (T), and although approved by the U.S. Food and Drug Administration, the potential increase in the temperature of the amniotic fluid with 3T imaging should be considered. 26, 38, 43, 44 Gadolinium is a class C molecule in pregnant women. It crosses the placenta and is excreted by the fetal kidney.…”
Section: Diagnostic and Prognostic Aspectsmentioning
confidence: 99%
“…It is strongly correlated to Gestational Age and its linear growth during gestation has been demonstrated on MRI also [15,16,1]. It is more accurate method of Gestational Age estimation than BPD, FL, HC and AC after 24th week of gestation [15,17]. Demographic data of the patient was recorded as name, age, occupation, socioeconomic status and obstetric history along with relevant history was recorded on pre designed and pre tested proforma.…”
Section: Original Research Articlementioning
confidence: 99%